Reflection of the Semantic Category of Quantity at the Word-Educational Level in the Modern Russian Language - Shevtsova Olga Vladimirovna (Researchparks Publishing, 2022)
The article deals with the content aspect of word formation, which is a system of word-formation meanings, united in word-formative categories, ways of expressing quantitative meanings.